Investigating intercalation mechanism of manganese oxide electrode in aqueous aluminum electrolyte. (10th February 2022) - Wang, Yijia; Ng, Kok Long; Dong, Tony; Azimi, Gisele
Abstract: Aqueous aluminum-ion batteries (AAIBs) are promising candidates for next-generation energy storage devices that are safe, cost effective, and environmentally benign. Among all electrode materials reported in AAIBs, transitional metal oxide-based electrodes are of particular interest. Although superior electrochemical performance had been achieved, the underlying charge storage mechanism involved remains equivocal. In this work, the electrochemical behavior and charge storage mechanism of alpha oxide dioxide (α-MnO2 ) electrode in aqueous aluminum trifluoromethanesulfonate (Al(OTF)3 ) electrolyte are comprehensively investigated through various electrochemical testing and extensive spectroscopic characterizations, and an alternative reaction mechanism is proposed. We observe that H3 O + intercalation/de-intercalation contributes to the reversible capacity over cycles, while only a small amount of Al 3+ could intercalate into α-MnO2 . The composition of the complex formed during discharge is proposed, which may contain Al 3+, OH −, and OTF − . This surface complex would dissolve after charge. Lastly, recommendations are made on prospective electrode and electrolyte design using the insights obtained from this study. Understanding the charge storage mechanism is crucial for designing appropriate electrode materials and electrolytes and we expect that our findings will shed light on achieving high-performance aluminum-based energy storage devices. Graphical abstract: Image, graphical abstract An alternative reversible H3O+ intercalation/de-intercalation mechanism of α-MnO2 in aqueous. Al-containing electrolyte is proposed and the surface complex composition is characterized for the first time.